2003
DOI: 10.1515/jpem.2003.16.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Type 2 Diabetes Mellitus in Thai Children and Adolescents Associated with Increasing Prevalence of Obesity

Abstract: Type 2 diabetes mellitus (DM) is being diagnosed more frequently in children and adolescents. Thailand has a low incidence of childhood DM. This study reviewed patients with DM in the Division of Pediatric Endocrinology, Faculty of Medicine, Siriraj Hospital compared to our previous study. The results demonstrate that type 2 DM in Thai children and adolescents has increased from 5% during 1986-1995 to 17.9% during 1996-1999. Mean age was 11.6 years. Mean BMI was 27.8 kg/m2. Fifty-six percent were diagnosed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 5 publications
3
54
0
Order By: Relevance
“…The patients with type 1 diabetes attended 3,109 assessments (median 2 assessments per patient, range [1][2][3][4][5][6][7][8][9][10][11][12]. Of the patients with type 2 diabetes, 36 had complications assessment (median 2, range 1-4), all had measurement of AER, 25 had gradable retinal photographs, 24 had peripheral nerve function testing, and 23 had autonomic nerve function testing.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients with type 1 diabetes attended 3,109 assessments (median 2 assessments per patient, range [1][2][3][4][5][6][7][8][9][10][11][12]. Of the patients with type 2 diabetes, 36 had complications assessment (median 2, range 1-4), all had measurement of AER, 25 had gradable retinal photographs, 24 had peripheral nerve function testing, and 23 had autonomic nerve function testing.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…A population-based incidence estimate from Western Australia demonstrated a 27% increase over 12 years from the early 1990s (5), and data from New South Wales indicate that ϳ1 in 10 adolescents with new-onset diabetes has type 2 diabetes (6). The majority of recent studies of youth-onset type 2 diabetes have addressed its epidemiology and etiology, and a strong association with the increase in childhood obesity is now widely recognized (3,7); however, few studies have addressed the prevalence and risk factors for microvascular complications in this age-group (8 -11).…”
mentioning
confidence: 99%
“…They reveal type 2 diabetes occurring in children as young as 8 years old (11). In addition, they have demonstrated a female preponderance (22)(23)(24), a strong family history of diabetes (22,25,26), and associations with obesity (11,22,(25)(26)(27), acanthosis nigricans (11,26,27), and polycystic ovary syndrome (PCOS) (28).…”
Section: Population-based Studiesmentioning
confidence: 99%
“…In Mexican-American youth aged 0 -17 years, a California clinic reported that 31% of the diabetic children had type 2 diabetes (32). Among newly diagnosed diabetic children and adolescents in Bangkok, type 2 diabetes increased from 5% of all cases during 1986 -1995 to 17.9% during 1996 -1999 (27). In contrast, among European populations, which have lower overall prevalences of type 2 diabetes, two very large studies have reported that only 0.5% of children and adolescents with diabetes have been classified as having type 2 diabetes (33,34).…”
Section: Population-based Studiesmentioning
confidence: 99%
“…A national survey in 2011 reported a prevalence of 7.6% overweight and 9% obesity among Thai children [10]. Many reports from various countries show increasing numbers and proportion of T2DM in the pediatric population, along with increasing childhood obesity [4,11,12].…”
mentioning
confidence: 99%